ERROR ANALYSIS ON THE DESCRIPTIVE WRITING OF THE SECOND SEMESTER STUDENTS OF STUDY PROGRAM OF ENGLISH UNIVERSITAS BRAWIJAYA - SAIFULLAH, CHRISTIANTO (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key Words: Error analysis, descriptive paragraph.The development of culture in this world recently gives impact to the development of language as well. Nowadays, many foreign languages have been learned in school and university in Indonesia. In producing language, sometimes the learners make some mistakes or error especially in using English as a foreign language. The researcher conducts a research on descriptive paragraphs written bythe Second Semester Students of Study Program of English Universitas Brawijaya by using Dulay, Burt dan Krashen’s (1982) theory. This research focuses on two problems: (1) What kinds of error are made by the 2nd Semester Students of Study Program of English in Descriptive writing, (2) What are the most frequent errors produced by the 2nd Semester Students of Study Program of English in Descriptive writing.This research uses qualitative approach in document analysis to describe the errors produced by the students in writing descriptive paragraphs. The data aresentences containing errors, taken from the descriptive paragraphs about “My Hobby” written by the students.The researcher found 509 errors divided into four categories. Error of misformation appears with the percentage of 47%, error of omission appears withthe percentage of 36%, error of addition appears with the percentage of 16% and error of misordering appears with the percentage of 1%.Based on the results, the writer suggests the next researchers especially students of English Department use other objects and other theories to see whether there are any significant different results.